Shari'ah position on ensuring presence of capital in joint equity based financing - Sadique, Muhammad Abdurrahman (Islamic Research and Training Institute (IRTI), Islamic Development Bank, 2009)
Islamic legal texts indicate that a joint venture involving monetary capital could be set in motion on the basis of capital that is existent and present, with clear agreement regarding the share of each partner. While gradual release of capital is admissible, prior existence of capital is necessary. Due to credit supplementing real money in a substantial manner, the identity of money in the current fiscal environment appears to have undergone significant change, the nature and influence of which need to be reassessed through a separate study. This is crucial for determining the form in which the existence and presence of capital could be ensured. The emphasis placed in Shari’ah on existence and presence of capital could indicate a measure for thwarting unwelcome monetary expansion, thus controlling inflation.